Effect of sequential thinnings in Pinus pseudostrobus Lindl. Stand - Pérez-Alavez, Yazmin; Rodríguez-Ortiz, Gerardo; Santiago-García, Wenceslao; Martin, Meredith P; Enríquez-del Valle, José Raymundo; Aguilar-Pinacho, Iván José (Ecosistemas y Recursos Agropecuarios, 2025)
Thinning is the silvicultural treatment that is most successful in a productive stand because it influences timber growth, biomass and leaf area. The objective was to evaluate the effect of sequential thinning on Pinus pseudostrobus stands in southern Mexico. In 2019, 30 trees were cut in 12 sites corresponding to four thinning levels; for each tree, We measured the following variables: needle and branch biomass and leaf area (LA) at the branch-tree level. Analysis of variance, tests of means (Duncan, 0.05) and regression analysis were performed. Trees from sites where 50% high (50A) thinning intensities (TI) were applied showed greater biomass accumulation (42.7 t ha-1) and LA (17.544 m2 ha-1); this same TI showed the greatest growth in diameter, basal area, accumulated volume and mean annual increase in basal area and volume. The best result in the P. pseudostrobus stand was the application of TI of 50% on the basal area, where the sites exceed 14 m2 ha-1. Sequential thinning over a five-year period in young stands magnifies timber yield.
Keywords: residual basal area; aboveground biomass; timber increase; thinning intensity; timber volume